2020
DOI: 10.21109/kesmas.v15i2.3937
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic-Comprehensive Approach: Best Practices to Improve Health Policy for COVID-19 Pandemic

Abstract: The COVID-19 pandemic affects entire communities and causes a huge impact on all life aspects which include biological, psychological, social, and spiritual well-being. Health systems and health policies are promising developments and opportunities to review progress and accelerate interventions in COVID-19 control. Studies devoted to core holistic-comprehensive issues surrounding this pandemic are limited. Therefore, this article aimed to review several best practice studies that reflect holistic-comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In comprehensive care, not only are all the patient's needs met but also their culture and spiritual well-being are considered to prevent their depression, improvement of physical condition, reduction of hospital stays, and faster recovery [24]. Te results of a review study also showed a holistic approach, including providing biological, psychological, social, and spiritual care, and healthcare, including preventive, curative, and rehabilitation services were considered to improve health policies during the epidemic [25]. Caregivers also used chemical or herbal remedies to reduce, alleviate, or heal patients, as well as methods such as massage, music therapy, patient dialogue, distraction, nutritional therapy, and other complementary therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In comprehensive care, not only are all the patient's needs met but also their culture and spiritual well-being are considered to prevent their depression, improvement of physical condition, reduction of hospital stays, and faster recovery [24]. Te results of a review study also showed a holistic approach, including providing biological, psychological, social, and spiritual care, and healthcare, including preventive, curative, and rehabilitation services were considered to improve health policies during the epidemic [25]. Caregivers also used chemical or herbal remedies to reduce, alleviate, or heal patients, as well as methods such as massage, music therapy, patient dialogue, distraction, nutritional therapy, and other complementary therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Global experiences clearly indicated that few countries with successful interventions were those who properly utilized multiple sectors. The ndings in studies elsewhere support this nding that to revert gross public problems such like COVID-19 need consolidated multisectoral efforts [29,30,31]. In similar manner the study in China also recommended better coordination, cooperation and strong solidarity in the joint efforts of ghting against COVID-19 [32].…”
Section: Discussionmentioning
confidence: 61%
“…This echoes with the study conducted by Salunke & Kumar expressed as leadership willingness and policy mandate are the necessary conditions and driving factor for accomplishment of multsectoral actions for a given project or program. [30].…”
Section: Discussionmentioning
confidence: 99%